The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.3990/1.9789036540131
|View full text |Cite
|
Sign up to set email alerts
|

Pre-sliding behaviour of multi asperity ceramic contacts

Abstract: functioning of high-tech mechatronic systems. The tribological behaviour of sliding contacts in such mechanisms plays an important role in the performance of these systems. The geometrical changes of the surfaces, where geometry is defined as a multi asperity contact, will influence the frictional behaviour. This thesis focuses on the pre-sliding and sliding behaviour of contacts with the aim of determining the parameters which influence the errors in positioning accuracy.The single asperity contact is the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…It is also worth mentioning that all curves, although starting from different point, end up in the same point on the horizontal axis which means that, for a rough contact, the static friction force is independent from the roughness rms. Using a multi asperity model, Winogrodzka showed that increasing the roughness rms at the contact of two rough surfaces increases the pre-sliding distance [46]. The same behavior is observed in Fig.…”
Section: A Rigid Smooth Ball On a Rough Elastic Half-spacesupporting
confidence: 70%
“…It is also worth mentioning that all curves, although starting from different point, end up in the same point on the horizontal axis which means that, for a rough contact, the static friction force is independent from the roughness rms. Using a multi asperity model, Winogrodzka showed that increasing the roughness rms at the contact of two rough surfaces increases the pre-sliding distance [46]. The same behavior is observed in Fig.…”
Section: A Rigid Smooth Ball On a Rough Elastic Half-spacesupporting
confidence: 70%